Reconstruction of Regulations in Legal Protection for Customers in the Event of Banking Liquidity Based on Justice - Sugiyanto Sugiyanto (Jurnal Ilmiah Dunia Hukum, 2023)
In this research article, we will attempt to present discussions related to the analysis of bank liquidity regulations based on applicable laws and regulations, analyze to understand the legal protection of depositors/customers when a bank liquidation occurs, and analyze the reconstruction of legal protection for customers in bank liquidation based on the principle of justice. The research method employed in this study is a sociological or non-doctrinal approach, where the primary focus is on collecting primary data. To obtain the necessary data for this research, the author utilized a juridical-empirical legal research method. In empirical research, the emphasis is on the application of law in the real field (law in concreto). The research was conducted by initially examining secondary data, followed by primary data research conducted in the field or within the community. The results of the research indicate that customer protection related to bank liquidation has been anticipated by the banks themselves through implicit and explicit protections, both of which have been explained and regulated in banking law. Bank Indonesia has the authority to provide guidance and supervision to ensure the continuity of bank operations, and Bank Indonesia also determines provisions related to the health of banks by considering aspects such as investors, asset quality, management, liquidity, for example, regarding customer protection and the provision of credit to customers, which is guided and supervised, affecting the health and smooth operation of banks. Therefore, there is a need for a restructuring of legal customer protection regulations in bank liquidation based on the principle of justice. Every bank is obligated to guarantee the funds of the public deposited with the respective bank. The government needs to organize Law Number 10 of 1998 concerning Banking, particularly the protection of bank customers in the case of liquidation, to be emphasized in banking management.